Edukasi Preventif Kekerasan Seksual dan Bullying di Lingkungan Sekolah - Azrita Mardhalena; Anny Riwayati; Dwi Nur Handayani; Mutmainnah Mutmainnah (GUYUB: Journal of Community Engagement, 2024)
Sexual violence and bullying were projected to increase significantly in 2023, particularly within school environments. This PKM initiative was conducted at SDN 28 Sungai Kakap, Sungai Kakap District, Kubu Raya Regency. The aim of this activity is to educate students about bullying behavior and sexual violence, as well as the psychological impacts caused by these behaviors. The activity utilized a lecture method accompanied by video and song media to facilitate understanding for children. The results of this PKM activity have shown a positive impact on students' knowledge about bullying behavior and sexual violence. Students were becoming increasingly aware of the negative impacts of these behaviors, aided by the media presented by the resource person in the form of videos and songs. Additionally, to motivate students and spread awareness to stop bullying behavior and sexual violence, the committee provided several prize packages.